2018
DOI: 10.1177/1457496918798203
|View full text |Cite
|
Sign up to set email alerts
|

Wound Closure after Thyroid and Parathyroid Surgery: A Meta-Analysis of Randomized Controlled Trials

Abstract: In the current study, no differences were found in patient satisfaction and postoperative pain among the subcutaneous suture, clip, and tissue adhesive wound closure methods. However, surgeons provided a more favorable appraisal for the subcutaneous suture method because of the improved cosmetic appearance. The choice of the closure method should be based on surgeon's preference and cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Huang et al . 23 performed a meta-analysis of nine RCTs, which included 612 patients, and illustrated the cosmetic advantage associated with using subcutaneous sutures to improve cosmesis versus staples. While these analyses provide some clarity with respect to cosmetic outcomes after thyroid and parathyroid neck closures, the present study reports the combined surgical and patient-reported outcomes of 18 RCTs through the adoption of NMA methodology of six different primary closure methods after neck surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al . 23 performed a meta-analysis of nine RCTs, which included 612 patients, and illustrated the cosmetic advantage associated with using subcutaneous sutures to improve cosmesis versus staples. While these analyses provide some clarity with respect to cosmetic outcomes after thyroid and parathyroid neck closures, the present study reports the combined surgical and patient-reported outcomes of 18 RCTs through the adoption of NMA methodology of six different primary closure methods after neck surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been previous systematic reviews and meta-analyses performed for determining the optimal wound closure 22 , 23 , there are several shortcomings to such studies: failure to include all available RCT data to inform outcomes; 22 and failure to implement a network meta-analysis (NMA) methodology to ensure robust evaluation of all potential closure methods. The advantage of an NMA is the simultaneous comparison of more than two treatments with a control or standard-of-care option 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The degree of scar hyperplasia after cleft lip surgery was positively correlated with anxiety [ 1 ]. The prevention and treatment of scar hyperplasia have been of great interest in cleft lip operations, and have been addressed by various means ranging from surgical suture materials to postoperative laser treatment [ 2 – 4 ]. However, current therapeutic measures were inadequate to resolve skin wound scar hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…1 Such concerns may cause self-consciousness in individuals undergoing cervicotomy (e.g., anterior neck surgery) for either thyroid or parathyroid disease. 2 Recent studies on reducing scar post-cervicotomy have utilized different techniques for surgical closure such as the use of synthetic glue, subcuticular and intradermal absorbable sutures, or adhesive strips. 3 , 4 However, a modest to no significant effect on reducing SF were reported; thus, aesthetic outcomes are still suboptimal and an alternative option might be able to address this gap.…”
Section: Introductionmentioning
confidence: 99%